The role of visceral hypersensitivity in the pathogenesis of irritable bowel syndrome - Alina A. Makarova ("Consilium Medicum" Publishing house, 2021)
This research includes visceral sensitivity and its mechanisms involved in the development of irritable bowel syndrome. Visceral hypersensitivity occupies the key place. The research has the description of etiological factors that form visceral hypersensitivity and also visceral sensitivity instrumental research methods, based on the use of the balloon dilation. The research also has the schemes of drug therapy for irritable bowel syndrome meanwhile the special attention is paid to the possible use of the sorbed probiotics and psychopharmacological drugs.